Rapid deployment of remote laser welding processes in automotive assembly systems. Issue 1 (2015) - Ceglarek, Dariusz; Colledani, Marcello; Váncza, József; Kim, Duck-Young; Marine, Charles; Kogel-Hollacher, Markus; Mistry, Anil; Bolognese, Luca
Abstract: Remote laser welding (RLW) has received increased attention in the recent years due to its benefits in terms of processing speed, lower investment, cost per stitch, and process flexibility. However, its potential in automotive assembly remains under exploited, mainly due to challenges involving system, process and fixture design, and part variation challenges. In this paper, an integrated rapid deployment framework for RLW process is proposed to improve ' right-first-time ' implementation of RLW in assembly systems. It enables closed-loop optimization of system layout, task assignment, fixture layout, process parameters, robot path planning and programming as an interlinked iterative approach. The results are demonstrated in an automotive door assembly pilot study.